POCUS Finding of Portal Venous Gas: An Unusual Consequence of an Amyloid Dysmotility Related Bezoar - Grace DeMarco; Qiuchen Jiang; Ernest Fischer (POCUS Journal, 2022)
A 73-year-old male with a recent finding of pericardial effusion and syncope was evaluated with point of care ultrasound for recurrent effusion. A thickened left ventricle and recurrent pericardial effusion were found. Unexpectedly, on scanning the inferior vena cava (IVC), extensive portal venous gas was identified, a finding previously described as a “meteor shower”. Subsequent imaging by computed tomography (CT) identified gastric edema and peri-gastric vessel gas as the source of the portal gas, attributed to a large bezoar. The bezoar was later classified as a phytobezoar and the patient was found to have both cardiac and gastrointestinal manifestations of light chain amyloidosis. The gastrointestinal amyloidosis predisposed the patient to bezoar formation owing to associated dysmotility, a rare complication of an unusual manifestation of systemic amyloid.